Optimasi Formulasi Sediaan Tablet Effervescent dari Ekstrak Etanol Tanaman Kalangkala (Litsea angulata) sebagai Antioksidan Menggunakan Metode SLD (Simplex Lattice Design): Optimization of Effervescent Tablets Formulation From Ethanol Extract of Kalangkala Plant (Litsea angulata) as Antioxidant Using SLD (Simplex Lattice Design) Method - Rohama Rohama; Melviani Melviani; Noval Noval (Jurnal Surya Medika (JSM), 2022)
Free radicals trigger various diseases, such as respiratory disorders and cancer. Aware of the bad potential of free radicals, many people consume antioxidants to tackle free radicals. One of them is Kalangkala Plant (Litsea angulata), which contains flavonoids. The potential of Kalangkala plants as antioxidants is formulated in effervescent tablets. The effervescent tablet was evaluated using the Simplex Lattice Design (SLD) method to determine the most optimal formulation. The results showed that the most optimal preparation from the evaluation of powders was F2, while the results of the evaluation of tablets using the SLD method were the most optimal was F3. In addition, the antioxidant activity test using the DPPH method showed that Kalangkala Leaf extract had strong antioxidant activity.